Peran Hedonic Shopping Motivation Sebagai Mediasi dalam Hubungan Antara Visual Merchandising dan Fear of Missing Out (FoMO) terhadap Impulse Buying pada Pengguna E-commerce Shopee di Kecamatan Lowokwaru, Malang - Resa Juniari; Rois Arifin; Nanik Wahyuningtyas (UNIVERSITAS ISLAM MALANG, 2026)
Abstract Rapid growth of e-commerce, particularly Shopee platform, has intensified impulse buying behavior influenced by external and psychological factors such as visual merchandising also FoMO. Examine effects of visual merchandising also FoMO on impulse buying also hedonic shopping motivation, as well as mediating role of hedonic shopping motivation among Shopee users in Lowokwaru District, Malang. A quantitative survey method was employed using questionnaires distributed to 100 active Shopee users and analyzed using PLS-SEM. Results indicate that visual merchandising significantly affects impulse buying (O = 0.240; t = 1.965; p = 0.049) and hedonic shopping motivation (O = 0.305; t = 2.663; p = 0.008), but hedonic shopping motivation does not mediate its effect on impulse buying. FoMO shows strongest influence on impulse buying (O = 0.346; t = 3.032; p = 0.002) and hedonic shopping motivation (O = 0.468; t = 4.521; p = 0.000), mediating effect of hedonic motivation is not significant. Findings suggest that external stimuli play a more dominant role than internal motivation in driving impulse buying behavior in e-commerce settings. Keywords: Impulse Buying,Visual Merchandising, FoMO, Hedonic Shopping Motivation.